2018
DOI: 10.1021/acssuschemeng.8b03211
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Influence on Palladium Doped Nickel Catalysts in Levulinic Acid Hydrogenation with Formic Acid as Hydrogen Source

Abstract: Levulinic acid (LA) is a platform molecule, and its valorization toward biofuel additives like γ-valerolactone or tetrahydrofuran is considered as an important step in planning future biorefinery schemes. In this study, various Ni based catalysts were studied for the LA hydrogenation with formic acid (FA) used as a hydrogen source. Two different ways of catalytic activity improvement are discussed (nickel loading vs addition of dopants). The influence of Ni doping by small amount of noble metals (Pt, Pd, Ru, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Furthermore, the presence of chlorine derived from the palladium precursor may facilitate the reduction of NiO x and inhibit the formation of the interfacial NiAl x O y spinel [18]. For the 4%Ni-1%Pd catalyst, a high-temperature effect was observed in the temperature range 220-350 • C associated with the reduction of NiO x species [20,21,32], so that modifying the Ni catalyst with Pd as dopant facilitated the reduction of nickel.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the presence of chlorine derived from the palladium precursor may facilitate the reduction of NiO x and inhibit the formation of the interfacial NiAl x O y spinel [18]. For the 4%Ni-1%Pd catalyst, a high-temperature effect was observed in the temperature range 220-350 • C associated with the reduction of NiO x species [20,21,32], so that modifying the Ni catalyst with Pd as dopant facilitated the reduction of nickel.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Monometallic Ni catalyst can be, however, modified by the addition of a second metal, that can result in the formation of new active sites and can increase the catalyst stability due to the establishment of intermetallic interactions and the modification of Ni interaction with the support. In particular, Ni-Pd catalysts showed higher activity and selectivity as compared to their single counterparts in the hydrogenation of both HMF [17] and LA substrates [18]. Mihet et al [19,20] showed that the introduction of small amounts (0.5%) of Pd and Rh noble metals to the 10% Ni/Al 2 O 3 catalyst reduces the crystallite size, with higher activity following in both NO reduction and CO 2 methanation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, its positive effect is recognized. Chlorine presence during the catalyst's synthesis can enhance the reducibility of Ni and improve its dispersion in the final catalyst [82]. On the other hand, the presence of chlorine in the reaction feed during the upgrade of pyrolysis products enhanced the sintering of nickel nanoparticles on the catalyst, which, in consequence, contributed to the activity decrease [62].…”
Section: Metal-based Catalystsmentioning
confidence: 99%
“…Lignocellulosic biomass is one of the most abundant renewable source of commodity chemicals [1,2] 5-(hydroxymethyl)furfural (HMF) that can be obtained via cellulose hydrolysis has been identified as valuable fuel, polymer, or chemical precursor. [3][4][5] Depending on the catalysts and reaction conditions HMF can be transformed towards a large variety of chemicals including 2,5-dimethylfuran (DMF), 5-methylfurfural (5-MF) or 2,5-bishydroxymethyltetrahydrofuran (BHMTHF) through hydrodeoxygenation (HDO) reaction (scheme 1).…”
Section: Introductionmentioning
confidence: 99%